Peningkatan Kemampuan Menulis untuk Menentukan Topik dalam Paragraf Melalui Pendekatan Contextual Teaching and Learning - Margono Margono; Ratu Wardarita; Dessy Wardiah (LPPM Universitas Trunojoyo Madura, 2021)
This study aims to improve writing skills to determine topics in paragraphs through a contextual teaching and learning approach to class VIII students at State Junior High School 8 Bayung Lencir, Muba. The method used is a class room action research method with data in the form of tests classified as quantitative data and data in the form of observations classified as qualitative data. Based on the results of data analysis that has been carried out on class VIII students of State Junior High School 8 Bayung Lencir, Muba from cycle I to cycle III there was a positive increase in each cycle of writing ability to determine topics in paragraphs through a contextual teaching and learning approach. Thus, there is an increase in the results of the writing ability test to determine the topic in the paragraph through a contextual teaching and learning approach